Analisis Hukum Putusan Nomor 27/Pdt.Sus-PHI/2022/PN.Jkt.Pst. Tentang Pemecatan Karyawan Secara Sepihak - Emir Syarif Fatahillah Pakpahan; Serli Tarigan; Ryenza Nafisah Az Zahra; Suci Rahma Dini (Fakultas Hukum, Universitas Warmadewa, 2025)
Unilateral termination of employment (PHK) is a crucial issue in industrial relations that can create legal uncertainty for both workers and employers. Although Indonesia’s labor regulations have established PHK procedures, discrepancies remain between normative provisions and their implementation, particularly concerning worker protection. This study aims to analyze Decision Number 27/Pdt.Sus-PHI/2022/PN.Jkt.Pst. to assess compliance with applicable regulations and its impact on workers affected by unilateral PHK. This research employs a normative juridical method with a case study approach and an analysis of relevant legislation. The findings indicate that the decision reinforces the importance of legally compliant PHK procedures and provides protection for disadvantaged workers. Further analysis reveals that inconsistencies in rule enforcement by employers are a primary factor leading to labor disputes. Therefore, this study highlights the need to strengthen legal enforcement mechanisms and worker protections to create a fairer and more balanced industrial relationship.